Single-Step EUS-Guided Transmural Drainage of Pancreatic Pseudocysts: Analysis of Technical Feasibility, Efficacy, and Safety (Gut and Liver, 2010)
Background/Aims: With the progress of product development, single-step endoscopic ultrasound (EUS)- guided transmural drainage can overcome some disadvantages of the blind or two-step procedures used in the treatment of pancreatic pseudocysts. We therefore evaluated the technical feasibility, efficacy, and safety of single-step EUS-guided transmural drainage of pancreatic pseudocysts. Methods: Endoscopic drainage of pancreatic pseudocysts was performed in 47 patients (median age, 46 years; range, 38 years to 59 years; 40 men) by using interventional echoendoscopes with a single-step device suitable for ballooning, bougination, and plastic-stent insertion. Results: Endoscopic stent placement was successful in 42 patients (89%; transgastric approach, 34/38; transduodenal approach, 8/9) and failed in 5 patients because of acute angulation (n=4) or small cyst (n=1). The volume of the pseudocyst was reduced by more than 90% or it disappeared completely in all of 41 patients (100%), based on a mean follow-up period of 17 months (range, 11 months to 20 months). The overall recurrence rate was 12% (5/41) after improvement by the procedure. Minor complications (one case of bleeding, three cases of pneumoperitoneum, and one case of peritonitis) occurred after the procedure in five patients (11%), but there were no major complications. Conclusions: Single-step EUS-guided transmural drainage can be used to treat pancreatic pseudocysts with acceptable feasibility, efficacy, and safety. (Gut Liver 2010;4:524-529)